ดนตรีราชสำนักของชาวเอเชียตะวันออกเฉียงใต้ - นาคะเสถียร กุลธิดา (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2020)
บทคัดย่อ ดนตรีราชสำนักของชาวเอเชียตะวันออกเฉียงใต้ พบว่า ได้มีการรับวัฒนธรรมของอารยธรรมอินเดียและจีนเข้ามาผสมผสานผ่านช่องทางการติดต่อค้าขาย การอพยพ การสู้รบและการเผยแพร่ศาสนา ส่งผลทำให้วัฒนธรรมดนตรีในภูมิภาคเอเชียตะวันออกเฉียงใต้เกิดการผสมผสานและพัฒนาจนกลายเป็นรูปแบบที่มีความเฉพาะ เป็นแหล่งการเรียนรู้ทางด้านวัฒนธรรมดนตรีที่มีความสำคัญ อันสามารถสะท้อนและบ่งบอกถึงความเจริญรุ่งเรืองของบ้านเมืองในอดีต โดยเฉพาะลักษณะเครื่องดนตรีในราชสำนักของชาวเอเชียตะวันออกเฉียงใต้ ซึ่งถือเป็นระเบียบแบบแผนและสืบทอดกันมาจนถึงปัจจุบัน โดยสามารถแบ่งได้เป็น 2 ลักษณะหลัก คือ 1) เครื่องดนตรีประเภทฆ้อง เป็นลักษณะทางดนตรีที่สามารถพบเห็นได้ในวงดนตรีราชสำนักและวงดนตรีพื้นเมืองของกลุ่มประเทศในแถบเอเชียตะวันออกเฉียงใต้ โดยเฉพาะประเทศที่เป็นหมู่เกาะ ซึ่งลักษณะเครื่องดนตรีส่วนใหญ่จะเป็นเครื่องดนตรีประเภทฆ้องมีปุ่ม มีการพัฒนาและประดับตกแต่งเครื่องดนตรีให้มีความสวยงามและมีขนาดที่หลากหลาย 2) เครื่องดนตรีประเภทระนาด เป็นลักษณะทางดนตรีที่ปรากฏในราชสำนักมาอย่างยาวนาน โดยสามารถพบเห็นได้ในทุกประเทศของเอเชียตะวันออกเฉียงใต้ โดยเฉพาะในกลุ่มประเทศที่เป็นแผ่นดินใหญ่ วัฒนธรรมการเล่นเครื่องดนตรีระนาด พบว่า มีพัฒนาการมายาวนาน โดยหลักฐานชิ้นสำคัญคือการค้นพบแท่งระนาดหินโบราณตามพื้นที่ต่าง ๆ ในภูมิภาค ซึ่งชี้ให้เห็นว่าในอดีตชาวเอเชียตะวันออกเฉียงใต้มีวัฒนธรรมการเล่นดนตรีและพัฒนาลักษณะของเครื่องดนตรีมาอย่างต่อเนื่องจนถึงปัจจุบัน คำสำคัญ : ดนตรีราชสำนัก, เอเชียตะวันออกเฉียงใต้ ABSTRACT Royal Court Music of Southeast Asian people found that the culture of Indian and Chinese civilization had been integrated through trading, migration, fighting and spreading the religion. As a result, music culture in Southeast Asia has been integrated and developed into a unique style and the area becomes a place to learn about the culture of music which is important to reflect and indicate the prosperity of the countries in the past especially the characteristics of musical instruments in the royal court of Southeast Asian people which have been formalized and inherited until the present. It can be divided into 2 main types which are 1) Gong instruments, a musical style that can be seen in the royal orchestras and local music bands in Southeast Asia especially the island countries. The characteristics of most musical instruments are gong-type instruments with buttons, developed, beautifully decorated, and varied in size. 2) Xylophone instruments are a musical style that has appeared in the royal court for a long time and can be seen in every country in Southeast Asia especially in the mainland countries. The culture of playing xylophone instruments has been developed for a long time. The main evidence is the discovery of ancient stone xylophone in different regions. This indicates that in the past, Southeast Asian people had a culture of playing music and developed the musical instruments style to be diverse and beautiful as continuing to date. Keywords: Royal Court Music, South-East Asia